Chronic gastritis and functional dyspepsia: is there an exit out of the dead spot? (reflections, blown together by Rome criteria III) - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To demonstrate contradictory issues of interrelation of «chronic gastritis» (CG) and «functional dyspepsia» (FD) concepts.Original positions. Notwithstanding what at the majority of FD patients have the signs of concomitant CG, foreign doctors do not use this diagnosis in clinical practice. On the contrary, in such cases the Russian doctors prefer to diagnose CG. Combination of specified diagnoses is most justified, which allows to estimate severity of morphological changes of mucosa of the stomach, to establish basic pathophysiological mechanisms of development of dyspeptic complaints, to determine optimal management approach.Conclusion. The problem of mutual relations between FD and CG has debatable character and deserves wide discussion.